Proximate Composition Study of Biscuits from Durian (Durio Zibethinus Murr.) Seed Flour as Food Innovation - Andi C. D. Pati; Irwan Said; Purnama Ningsih; Sitti Aminah; Sri Mulyani (Universitas Tadulako, 2025)
Biscuits are one of the most popular snacks for the public, with the primary raw material being wheat flour. However, the high dependence on wheat flour encourages the need to find alternative ingredients that are more diverse and have high nutritional value. This study aims to analyze the proximate content (carbohydrate, protein, and fat) of biscuits made from durian seed flour (TBD), which is compared with cornstarch (TM) and wheat flour (TT). Proximate analysis methods included UV-Vis spectrophotometry for carbohydrate analysis, the Kjeldahl protein method, and Soxhlet fat extraction. The formulations used consisted of: F1 (100% TBD), F2 (100% TM), F3 (50% TBD:50% TM), and F4 (50% TT:50% TM). The results showed that the highest carbohydrate content was found in F1 at 70.07%, while the highest protein content in F4 at 13.65%. The highest fat content was found in F2 at 21.69%. The best formulation was obtained in F3 (50% TBD:50% TM) because it has a balanced nutritional composition and potential as a functional food product, especially for people with diabetes. In addition, this biscuit product has the potential as a contextual learning medium in food science and nutrition, especially in introducing proximate concepts and utilizing tropical fruit seed waste.